Immune checkpoint inhibition: Prospects for prevention and therapy of hepatocellular carcinoma - Elsegood, Caryn; Tirnitz-Parker, Nina; Olynyk, John; Yeoh, G. (2017)
The global prevalence of liver cancer is rapidly rising, mostly as a result of the amplified incidence rates of viral hepatitis, alcohol abuse and obesity in recent decades. Treatment options for liver cancer are remarkably limited with sorafenib being the gold standard for advanced, unresectable hepatocellular carcinoma but offering extremely limited improvement of survival time. The immune system is now recognised as a key regulator of cancer development through its ability to protect against infection and chronic inflammation, which promote cancer development, and eliminate tumour cells when present. However, the tolerogenic nature of the liver means that the immune response to infection, chronic inflammation and tumour cells within the hepatic environment is usually ineffective. Here we review the roles that immune cells and cytokines have in the development of the most common primary liver cancer, hepatocellular carcinoma (HCC). We then examine how the immune system may be subverted throughout the stages of HCC development, particularly with respect to immune inhibitory molecules, also known as immune checkpoints, such as programmed cell death protein-1, programmed cell death 1 ligand 1 and cytotoxic T lymphocyte antigen 4, which have become therapeutic targets. Finally, we assess preclinical and clinical studies where immune checkpoint inhibitors have been used to modify disease during the carcinogenic process. In conclusion, inhibitory molecule-based immunotherapy for HCC is in its infancy and further detailed research in relevant in vivo models is required before its full potential can be realised.